PENGARUH DOSIS PUPUK KASCING DAN NITROGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (LACTVCA SATIVA L.) VAR GEORGIA - Winten, Ketut Turaini Indra (Agriculture Faculty of Flores University, 2008)
The low of growth and yield of lettuce is quite often caused by the low of soil fertility, especially nitrogen and C-organic content. Poor soil physical properties also contribute to the cause of low yield of lettuce. Improved soil physical and chemical properties by adding casting fertilizers and nitrogen are expected to be able to increase the yields of lettuce. The field experiment was conducted in Candikuning village, district of Baturiti, Tabanan regency, from October 2005 to January 2006. The objective of the experiment was to study the effect of casting fertilizer and nitrogen rates on the growth and yields of lettuce. A randomized complete block design was used in this experiment and two treatment factors were imposed. Those two treatment factors were rates of casting fertilizers (i.e. 0, 10, 20 and 30 t ha